Palliative and Critical Care: Their Convergence in the Pediatric Intensive Care Unit - Buang, Siti Nur Hanim; Loh, Sin Wee; Mok, Yee Hui; Lee, Jan Hau; Chan, Yoke Hwee (Frontiers in Pediatrics, 2022)
Palliative care (PC) is an integral component of optimal critical care (CC) practice for pediatric patients facing life-threatening illness. PC acts as an additional resource for patients and families as they navigate through critical illness. Although PC encompasses end of life care, it is most effective when integrated early alongside disease-directed and curative therapies. PC primarily focuses on improving quality of life for patients and families by anticipating, preventing and treating suffering throughout the continuum of illness. This includes addressing symptom distress and facilitating communication. Effective communication is vital to elicit value-based goals of care, and to guide parents through patient-focused and potentially difficult decision-making process which includes advanced care planning. A multidisciplinary approach is most favorable when providing support to both patient and family, whether it is from the psychosocial, practical, emotional, spiritual or cultural aspects. PC also ensures coordination and continuity of care across different care settings. Support for family carries on after death with grief and bereavement support. This narrative review aims to appraise the current evidence of integration of PC into pediatric CC and its impact on patient- and family-centered outcomes. We will also summarize the impact of integration of good PC into pediatric CC, including effective communication with families, advanced care planning, withholding or withdrawal of life sustaining measures and bereavement support. Finally, we will provide a framework on how best to integrate PC in PICU. These findings will provide insights on how PC can improve the quality of care of a critically ill child.